MODEL PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL PADA LEMBAGA PENDIDIKAN ISLAM - Ida Zahara Adibah; Mohamad Johan Saril; Uswatun Chasanah (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT This article aims to examine the conceptual foundations and multicultural values relevant to Islamic Religious Education (PAI) curriculum development, and to formulate a multicultural-based PAI curriculum development model applicable to Islamic boarding schools (pesantren), schools, and madrasahs. The method employed is a Systematic Literature Review (SLR) using the PRISMA protocol, involving 28 selected articles from 381 initial articles sourced from Scopus, Google Scholar, and SINTA databases for the period 2020–2025. The findings indicate that: (1) the conceptual foundations of multicultural PAI curriculum derive from universal Islamic values such as tasamuh, ukhuwah, ta'aruf, ta'awun, and rahmatan lil 'alamin, integrated with Banks' multicultural theory and Tyler's curriculum development framework; (2) the formulated model encompasses five core components: (a) Islamic multicultural value orientation, (b) inclusive curriculum objectives, (c) integrative content based on local wisdom, (d) dialogical-participatory learning strategies, and (e) authentic character-based assessment. This model is adaptive and can be implemented across Islamic educational institutions with contextual adjustments. The findings are expected to serve as a reference for curriculum developers, educators, and policymakers in strengthening inclusive, moderate, and multiculturally-oriented Islamic education. ABSTRAK Artikel ini bertujuan mengkaji landasan konseptual dan nilai-nilai multikultural yang relevan dalam pengembangan kurikulum Pendidikan Agama Islam (PAI), serta merumuskan model pengembangan kurikulum PAI berbasis multikultural yang dapat diaplikasikan pada pesantren, sekolah, dan madrasah. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan protokol PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), melibatkan 28 artikel terpilih dari 381 artikel awal yang bersumber dari database Scopus, Google Scholar, dan SINTA periode 2020–2025. Hasil kajian menunjukkan bahwa: (1) landasan konseptual kurikulum PAI multikultural bersumber dari nilai-nilai Islam universal seperti tasamuh, ukhuwah, ta'aruf, ta'awun, dan rahmatan lil 'alamin, yang diintegrasikan dengan teori multikultural Banks dan kerangka pengembangan kurikulum Tyler; (2) model yang dirumuskan mencakup lima komponen inti: (a) orientasi nilai Islam multikultural, (b) tujuan kurikulum inklusif, (c) konten integratif berbasis kearifan lokal, (d) strategi pembelajaran dialogis-partisipatif, dan (e) evaluasi autentik berbasis karakter. Model ini bersifat adaptif dan dapat diterapkan lintas lembaga pendidikan Islam dengan penyesuaian kontekstual. Temuan ini diharapkan menjadi rujukan bagi pengembang kurikulum, pendidik, dan pembuat kebijakan dalam memperkuat pendidikan Islam yang inklusif, moderat, dan berwawasan multikultural.